Penggunaan Metode Kooperatif Picture And Picture Guna Meningkatkan Kualitas Pembelajaran - Suryani Suryani (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
In the teaching and learning process of Social Sciences, many problems are carried out by the teacher. One of them is some students still rely on their teacher's activities in learning, so the role of students is still very lacking. Even thought, the teacher always involving students to play an active in learning process. In contrary, students assume that the subject of Social Sciences is very boring. So that this causes a low quality of learning in Social Sciences, especially in  SMP Negeri 21 Pontianak. This cases has tickled the writer to take the theme of research on picture and picture cooperative methods to improve the quality of learning and increase the interest and activity of students in teaching and learning activities in Social Sciences.As for the techniques used of data collection is through observation by teachers and collaborators. The research involved two cycles of 42 students. While the data analysis used description with percentage techniques. Furthermore the level of activity of students and teachers is expressed in the category of "very good", "good" or "moderate", while the success of using picture and picture cooperative methods is stated as "successful", "less successful", or "unsuccessful".The results of this reseacrh with picture and picture cooperative methods have been successful, which is showing indicated by an increase in student activity of learning because it has reached the specified criteria is 81% of students are actively involved, while teacher activities reach 86.53%, as well as student learning outcomes with a value of 78.57, where this shows that it is exceeding the KKM value of 72, with a percentage of completeness of 76%, which has exceeded the criteria of 75%.